The Monastic Architecture of the Order of the Poor Ladies — Later Called the ‘Poor Clares’ — in Central Italy between 13th and 14th Centuries - Danesi, Valeria (Actual Problems of Theory and History of Art, 2017)
At the dawn of the 13th century the male monasticism was living a new era, marked by the advent of St. Francis and St. Dominic and characterized by a return to the poorest and humble roots of Christianity as well as by greater openness towards the believers, more than the closed dimension of the monastery. A new female religious movement, known as ‘the Poor Ladies’, was born in Central Italy in the same years, under the guidance of St. Clare of Assisi. The movement did not join any of the existing monastic rules at the beginning, even though it was strictly bound to the Franciscan experience and had total poverty as its highest and exclusive aspiration. The Church of Rome saw a possible critical issue in the movement and in its lack of control. It tried to regulate it at the Council of Lateran IV in 1215, especially with the Cardinal Bishop of Ostia Ugolino dei Segni (the future Pope Gregory IX), an essential figure for the history and evolution of the female monasticism who imposed the cloistered life on all female monastic orders. The analysis of the architecture of the so-called ‘PoorLadies’ is, therefore, fundamental in order to understand the consequences of this imposition. New liturgical spaces for females only, in fact, started to be created in both the existing convents and in the newly built ones with the aim of protecting the daily life of the nuns. The arrangement of the preexisting spaces in St. Damianoin Assisi — the cradle of the order of St. Clare — was purely random but led anyway to the creation of proper architectural models, later exported in other convents of the same order. The nuns’ choir in St. Damiano, infact, is located outside the ecclesiastical perimeter in order to preserve the cloistered dimension. However, this peculiar position of the choir made it quite difficult for the nuns to assist to the liturgical functions from the beginning, but the issue was solved only during the 14th century with the ‘migration’ of this liturgical space to a new position, after a series of different solutions.
Keywords: St. Clare of Assisi; Poor Ladies order; Assisi; monastic architecture; female monastic